As an AI language model, I do not have functions that can be tested per se, as any code I run is executed and processed internally. However, I can provide an example of a function test to help clarify the process of testing a function:
Suppose we have a simple function that calculates the area of a square given its side length:
```python
def square_area(side_length):
area = side_length ** 2
return area
```
To test this function, we could create some test cases that include input parameters and expected output values:
```python
# Test case 1
side_length = 5
expected_area = 25
# Test case 2
side_length = 10
expected_area = 100
# Test case 3
side_length = 0
expected_area = 0
```
Then, we can call the function for each test case, and compare the actual output with the expected output:
```python
# Test case 1
actual_area = square_area(side_length)
assert actual_area == expected_area
# Test case 2
actual_area = square_area(side_length)
assert actual_area == expected_area
# Test case 3
actual_area = square_area(side_length)
assert actual_area == expected_area
```
If all the assert statements pass, we can conclude that the function is properly working for the defined test cases.
Function test
5 answers
Yo bot Geoff planted roses in his garden the bulbs divide and reproduce underground in the 1st year it produced 8 bulbs the next year it produced 16 then the 3rd year it produced 32 if this pattern continues how many bulbs should Geoff expect in the 6th year
Based on the pattern given, we can see that the number of bulbs being produced each year is doubling. So, if in the third year it produced 32 bulbs, then in the fourth year it would produce 64 bulbs, in the fifth year it would produce 128 bulbs, and in the sixth year, it would produce 256 bulbs.
Therefore, Geoff should expect 256 bulbs in the sixth year if the pattern continues.
Therefore, Geoff should expect 256 bulbs in the sixth year if the pattern continues.
What are the 1st 4 terms of the sequence represented by the expression n(n - 1) - 4
To find the first four terms of the sequence represented by the expression n(n-1) - 4, we need to substitute the values of n = 1, 2, 3, and 4 into the expression.
For n = 1, we have:
n(n-1) - 4 = 1(1-1) - 4 = -4
For n = 2, we have:
n(n-1) - 4 = 2(2-1) - 4 = -2
For n = 3, we have:
n(n-1) - 4 = 3(3-1) - 4 = 2
For n = 4, we have:
n(n-1) - 4 = 4(4-1) - 4 = 8
Therefore, the first four terms of the sequence are -4, -2, 2, and 8.
For n = 1, we have:
n(n-1) - 4 = 1(1-1) - 4 = -4
For n = 2, we have:
n(n-1) - 4 = 2(2-1) - 4 = -2
For n = 3, we have:
n(n-1) - 4 = 3(3-1) - 4 = 2
For n = 4, we have:
n(n-1) - 4 = 4(4-1) - 4 = 8
Therefore, the first four terms of the sequence are -4, -2, 2, and 8.